Primary Hepatic Lymphoma: an unusual hepatic malignancy- case report and review of literature - Abhishek Purohit; Mukul Aggarwal; Manoranjan Mahapatra; Pravas Mishra; Tulika Seth; Arun Kumar Dinda (Mediterranean Journal of Hematology and Infectious Diseases)
Primary Hepatic lymphoma (PHL) is a very rare malignancy representing approximately 0.016% of all cases of Non Hodgkin Lymphoma (NHL). It oftens presents in elderly persons with signs and symptoms of hepatitis, primary liver cancer or metastatic tumor. In this case report, we present a 58 year old lady with poor performance status who presented with obstructive jaundice, epigastric pain and bilious vomiting. Abdominal imaging revealed a large hepatic mass that was pathologically confirmed primary hepatic diffuse large B cell lymphoma without bone marrow involvement. Because of severe jaundice, she was managed with Rituximab, cyclophosphamide and prednisolone based therapy, but succumbed to neutropenic fever following chemotherapy.